THE EFFECT OF FINANCIAL PERFORMANCE OF LOCAL GOVERNMENT ON THE PROPORTION OF DISKRESIONER FUND - Taherawan, Habelki Sinaga (International Journal of Public Budgeting, Accounting and Finance, 2018)
The objective of the research was to analyze the influence of Local Financial Performance proxied by Local Dependency Ratio, Intergovernmental Revenue, SiLPA’s Financing, and Fiscal Space Ratio with the Status of Regional Head as moderating variable on the  Proportion of Discretionary Fund. The population was 51 districts/cities of North Sumatera Province that were approaching the election of regional heads (Pilkada) from  2010 to 2015, and all of them were used as the samples, taken by using saturated sampling technique. The data were analyzed by using multiple regression and residual test. The result of the research showed that the variables of Local Dependency Ratio, Intergovernmental Revenue, SiLPA’s Financing, and Fiscal Space Ratio simultaneously had significant influence on the Proportion of Discretionary Fund. Partially, the variable of Local Dependency Ratio did not have any influence on the Proportion of Discretionary Fund, while the variables of Intergovernmental Revenue, SiLPA’s Financing, and Fiscal Space Ratio had positive and significant influence on the Proportion of Discretionary Fund. The status of Regional Heads could not moderate the influence of the variables of Local Dependency Ratio, Intergovernmental Revenue, SiLPA’s Financing, and Fiscal Space Ratio on the Proportion of Discretionary Fund.